Stellarex drug-coated balloon for treatment of femoropopliteal arterial disease—The ILLUMENATE Global Study: 12-Month results from a prospective, multicenter, single-arm study - Schroë, H.; Holden, A.; Goueffic, Y.; Jansen, Shirley; Peeters, P.; Keirse, K.; Ito, W.; Vermassen, F.; Micari, A.; Blessing, E.; Jaff, M.; Zeller, T. (2018)
© 2017 The Authors. Catheterization and Cardiovascular Interventions Published by Wiley Periodicals, Inc. Objectives: The purpose of this study was to assess the safety and performance of Stellarex Drug-coated balloon (DCB). Background: DCB coatings differ in excipients, paclitaxel dose, and coating morphologies. Due to these differences, a class effect with DCBs has not been demonstrated. Consequently, each DCB needs to be evaluated independently based on its own clinical study results. Methods: The ILLUMENATE Global Study is a prospective, multicenter, single-arm study. Patients with intermittent claudication or ischemic rest pain due to superficial femoral artery (SFA) and/or popliteal peripheral artery disease (PAD) were treated with the Stellarex DCB. The primary efficacy endpoint was primary patency, defined as freedom from restenosis with peak systolic velocity ratio =2.5 or clinically-driven target lesion revascularization (CD-TLR) at 12 months. The primary safety endpoint was freedom from device and procedure-related death through 30 days postprocedure and freedom from target limb major amputation and CD-TLR through 12 months. Results: In total, 417 lesions were treated in 371 patients. The mean lesion length was 7.5 ± 5.3 cm, 40.8% of lesions were severely calcified per core laboratory fluoroscopy criteria and 31.3% were total occlusions. Primary patency by independent duplex core lab evaluation was 81.4% and the freedom from CD-TLR was 94.8% day 365 per Kaplan-Meier estimate. The majority of patients experienced improvements in their Rutherford classification (90.3%) and walking impairment questionnaire score (83.6%) at 12 months compared to baseline. Conclusions: This study validated previous positive findings and confirms the strong safety profile and effectiveness outcomes.